Banker to the poor micro-lending and the battle against world poverty - Yunus, Muhammad (New York PublicAffairs, 2007)
Muhammad Yunus is that rare thing: a bona fide visionary. His dream is the total eradication of poverty from the world. In 1983, against the advice of banking and government officials, Yunus established Grameen, a bank devoted to providing the poorest of Bangladesh with minuscule loans. Grameen Bank, based on the belief that credit is a basic human right, not the privilege of a fortunate few, now provides over 2.5 billion dollars of micro-loans to more than two million families in rural Bangladesh. Ninety-four percent of Yunus's clients are women, and repayment rates are near 100 percent. Around the world, micro-lending programs inspired by Grameen are blossoming, with more than three hundred programs established in the United States alone.
Reprint. Originally published: 1999.
Keywords: Yunus, Muhammad, 1940-